Effects of accelerated environmental aging on glass fiber reinforced thermoset polyurethane composites. (1st June 2016) - Nicholas, J.; Mohamed, M.; Dhaliwal, G.S.; Anandan, S.; Chandrashekhara, K.
Abstract: In the present study, the effects on the microstructure and the impact behavior of thermoset polyurethane composite material, exposed to an accelerated aging environment, were assessed. A combined hygrothermal and ultraviolet (UV) chamber is used in an accelerated aging procedure to simulate temperate climate conditions. The samples were manufactured using a vacuum assisted resin transfer molding (VARTM) technique using a novel two-part polyurethane resin (Methylene diphenyl diisocyanate/Polyol) infused into plane weave E-glass fiber mats. Samples were exposed to the UV/moisture rich environment for 250, 500, 750 and 1000 h. Effect of UV exposure on color change of composite specimens was evaluated using colorimetry. The rate of color change and the total change in color for the fiber reinforced composite was shown to be much less than that of pure polyurethane. Optical microscopy observations revealed that the color change was limited to surface discoloration due to the fiber reinforcement limiting degradation to the surface polymer matrix microstructure even after extended UV-exposure. The accelerated aging effect on the glass fiber reinforced polyurethane was examined using low velocity impact tests to evaluate impact properties of the material throughout the aging process. The test showed that the bulk composite material was resistant to the UV aging by demonstrating no significant change in impact properties due to the accelerated aging process.